The Effect of Static Stretching in Agility and Isokinetic Force at Football Players - Sami Sermaxhaj; Fitim Arifi; Alaj Iber; Abedin Bahtiri; Jeton Havolli; Suela Sermaxhaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The repercussion is an essential of the football training, also called "Cool Down". Static stretching and slow running are typical activities of this section, but in the last few years static stretching has had a great infl uence on performance functionality and is one of the most debated topics in sports sciences and medicine. The aspiration of this research is to show the impact of recovery associated with static stretching and the agility performance of young football players. This research was conducted between August and November with a sample of 20 players age 12.1±0.3 years (range 11-13 years) separated into two groups- control and experimental. First measurements that have been initiated are body weight 40.6±6.5 kg, height 152.6±6.9 cm and agility performance (Ajax test 5x10 m and zig-zag test with and without ball). Agility was measured with electronic photocells', with a measurement of .01 sec. Experimental testing proposed that both groups have completed the regular training program, while the experimental group (despite the control group) during the recuperation (cool down) except running, they conveyed out the experimental treatment / static stretching exercises. Each exercise lasts at least 20 seconds. After completing the experimental program members in both groups underwent fi nal measurements. The results that were reached by univariate analysis of variance (ANOVA) at initial and fi nal measurements, have shown insignifi cant statistical values between the control and experimental group in the agility performance.